Proposing a Land Suitability Analysis Method for Green Open Space in Nusantara Capital City - Muhammad Taufiqurrohman; I Nyoman Teguh Prasidha; Atie Tri Juniati (Fakultas Teknik Universitas Pancasila, 2025)
Green open spaces are regarded as infrastructures that have a major positive impact on urban residents' quality of life and the sustainability of urban growth. Green open spaces play an important role in Nusantara Capital City with the theme of forest city. Examining any techniques employed in earlier research is crucial to determining the accurate location. Understanding the different approaches should enable one to suggest ways for further research in land suitability for green open spaces. We used the literature review of twenty relevant international papers from 2016 to 2023 as our method. In line with previous research, the study's findings show that the analytical hierarchy process is the most popular method employed for land suitability analysis for green open space in Nusantara Capital City. The evaluation criteria that suit Nusantara Capital City are elevation, slope, land use land cover, accessibility, water bodies, and population. The analytical hierarchy process can help further research in land suitability analysis for green open space in Nusantara Capital City.